2021
DOI: 10.1007/s00170-021-08148-2
|View full text |Cite
|
Sign up to set email alerts
|

The central strain analytical modeling and analysis for the plate rolling process

Abstract: The strain after rolling plays an important role in the prediction of the microstructure and properties and plate deformation permeability. So it is necessary to establish a more accurate theoretical strain model for the rolling process. This paper studies the modeling method of the equivalent strain based on the upper bound principle and stream function method. The rolling deformation region is divided into three zones (inlet rigid zone, plastic zone, and outlet rigid zone) according to the kinematics. The bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Big data is a product that emerged in the process of modern high-tech development and has strong market potential, and through relevant practical analysis, it is found that big data can play an important role in the process of urban planning. First, the government can use big data technology to understand and master the problems that arise in the process of urban spatial planning, make timely decisions, and deal with these problems [1]. Secondly, in the traditional model, the information channel is single, and the accuracy of the data obtained is limited, which can no longer match the requirements of modern urban planning; the application of big data technology can quickly expand the information and sources of urban and rural planning data.…”
Section: Introductionmentioning
confidence: 99%
“…Big data is a product that emerged in the process of modern high-tech development and has strong market potential, and through relevant practical analysis, it is found that big data can play an important role in the process of urban planning. First, the government can use big data technology to understand and master the problems that arise in the process of urban spatial planning, make timely decisions, and deal with these problems [1]. Secondly, in the traditional model, the information channel is single, and the accuracy of the data obtained is limited, which can no longer match the requirements of modern urban planning; the application of big data technology can quickly expand the information and sources of urban and rural planning data.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al [17] gained the velocity field of the fixed angle of the chamfered edge using the flow function method, derived the dog-bone shape coefficient from the volume invariant condition, and then obtained the plastic deformation power, shear force and friction force separately using the equal yield criterion. Jiang et al [18] modified the boundary conditions of the adjacent deformation region in order to establish the near-real kinematic allowable velocity field using the flow function method. Sezek et al [19] set up the three-dimensional deformation of the plate rolling process utilizing the upper bound theorem.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of roll offset, speed ratio, depression amount and roll radius on the curvature of the plate are studied by using the nite element model during the snake rolling process. Jiang et al [15] studied the modeling method of the equivalent strain of the synchronous rolling based on the upper bound principle and ow function method. Sun et al [16] used the ow function method to analyze the rheological properties of the cast-rolled deformation zone, and established the velocity eld of the cast-rolled zone.…”
Section: Introductionmentioning
confidence: 99%